Offenders’ Inability to Pay Restitution to Victims: An Islamic Criminal Law Perspective - Dinda Sherin Al Asya Sinaga; Zaid Alfauza Marpaung (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
This study examines the problem of offenders’ inability to fulfill restitution obligations to victims from the perspectives of Indonesian positive law and Islamic criminal law. The study is motivated by the limited effectiveness of restitution enforcement within the Indonesian legal system, which remains heavily dependent on the offender’s financial capacity, resulting in the suboptimal fulfillment of victims’ rights in practice. This research aims to analyze the regulation of restitution under Indonesian positive law and to explore the concept of diyat in Islamic criminal law as an alternative approach to addressing offenders who are unable to pay restitution. This study employs normative legal research using statutory, conceptual, and comparative approaches, analyzed qualitatively through library research. The findings reveal that Indonesian positive law positions restitution as a form of individual criminal responsibility without providing a comprehensive mechanism for situations in which offenders lack the financial capacity to satisfy such obligations. Consequently, the fulfillment of victims’ rights frequently remains ineffective in practice. In contrast, Islamic criminal law offers a more flexible and restorative approach through mechanisms such as the postponement of payment for individuals experiencing economic hardship, as reflected in Qur’an Surah Al-Baqarah (2): 280, the concept of ʿāqilah as a form of collective responsibility, and the potential involvement of social institutions in ensuring the fulfillment of victims’ rights. This study argues that the principles of Islamic criminal law possess significant relevance for the development of a restitution system that is more equitable, humane, and victim-oriented while simultaneously taking into account the offender’s economic circumstances.